Preemptive bribery and incomplete information: Does prior knowledge matter?. (7th February 2017) - Mishra, Ajit; Samuel, Andrew
Abstract : This paper studies bribery between a firm and a supervisor who monitors the firm for regulatory compliance. Bribery occurs preemptively, that is before the supervisor exerts costly effort to discover the firm's level of noncompliance and collect evidence for successful prosecution. In contrast to previous papers, preemptive bribery is modeled as a Bayesian signaling game because the supervisor is uninformed about the firm's level of noncompliance. We show that under normal informational assumptions, some (possibly all) firms always engage in preemptive bribery. However, if knowledge of the firm's level of noncompliance has implications for the supervisor's ability to collect evidence and prosecute (prior knowledge), preemptive bribery can be completely eliminated. Results which apply to preemptive bribery under complete information do not apply here.